Differential expression of LEF1/TCFs family members in colonic carcinogenesis. Issue 11 (22nd May 2017) - Han, Wenxiao; He, Longmei; Cao, Bangrong; Zhao, Xinhua; Zhang, Kaitai; Li, Yan; Beck, Paul; Zhou, Zhixiang; Tian, Yantao; Cheng, Shujun; Wang, Hongying
Abstract : Lef1/Tcfs family, which includes Lef1, Tcf1, Tcf3, and Tcf4, is required for the transcriptional activation induced by β‐catenin. However, whether all the members play the same role in colon carcinogenesis is not clear. We found that Lef1 and Tcf1, but not Tcf3 and Tcf4, were upregulated at both mRNA and protein level with the formation of colon tumor in AOM‐DSS mouse model. The same profiles were seen in human specimens with the evolvement from adenoma to adenocarcinoma. Additionally, Lef1 and Tcf1 were correlated with a subgroup of Wnt target genes, including Lgr5, a key gene of intestinal stem cell. Further studies supported the role of Tcf1 on sphere formation and transcriptional regulation of Lgr5 in vitro. Interestingly, 3′ UTR of each Lef1/Tcfs member were targeted by diverse miRNAs, which were negatively correlated with respective member in human colon cancer specimens. Furthermore, these miRNAs were verified to repress Tcf1 and Lef1 in vitro. Taken together, Lef1 and Tcf1 showed oncogenic effect in colonic carcinogenesis. Cellular context of miRNAs might play important roles in carcinogenesis by altering the expression pattern of Lef/Tcfs members. © 2017 Wiley Periodicals, Inc.